PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT RODAMAS MAKMUR MOTOR DI KOTA BATAM - Lahagu, Ferianus; Triana Ananda Rustam (LPPM Universitas Putera Batam, 2022)
Every company wants employee performance to continuously improve in order to achieve the firm’s goals.This research aims to analyze the impact of compensation and work motivation on worker performance at PT Radomas Makmur Motor. Quantitative study is a kind of study with a population of 150 person. Data collectors make use of questionnaires and this reserach using a saturated sample technique, which means that the entire population is sampled. The data was processed using SPSS 25 with the yield of compensation t arithmetic > t table of 6.432 > 1.655 with a significance worth of 0.000 <0.05 which means that compensation has a positive and significant impact on worker performance. Work motivation has a t count > t table of 4.023 > 1.655 with a significance of 0.000 <0.05, which means that work motivation has a positive and significant impact on employee performance. As well as compensation and work motivation together have a positive and significant impact on worker performance as indicated by the yield of the F test with an F value of 86.347> Ftable 2.66 with a significance of 0.000 <0.05 and the R worth of 0.54 or 54%. 2